READING STRATEGIES FOR CRITICAL READING - Bambang A. Loeneto (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
This paper discusses and shares some strategies of teaching critical reading which are hopefulll, useful for teachers of English in having their students actively involved in reading activity in their classrooms. In high schools- SMPs or SMAs, teachers typically teach their students to read receptively. to read for information. What's more, many freshman students have not been taught to read actively or critically to construct knowledge as they read. Students gain knowledge by memorizing the statements r.vithirr a text. For them. as non-critical readers, texts provide facts. For critical readers, any text depicts the facts. They also recognize not only rvhat a text says, but also how that text portrays the issue described in it. A text is written in various ways as a typical creation of a unique author. For example, a non-critical reader might read a history book to leam the facts of the situation or to discover an accepted interpretation of those events. Whereas a critical reader might read the same work to appreciate how a particular perspective on the events and a pafiicular selection of f-acts can lead to particular understanding. The reading strategies for critical reading aim to allow students recognize an author's purpose, understand tone and persuasive elements, and recognize bias. These goals actually. refers to something on the page. Each requires inferences from evidence lvithin the text.Critical reading is not simply close and careful reading. To read critically. one must actively recognize and analyze evidence upon the page.